ALGORITMA KRIPTOGRAFI AES RIJNDAEL - Surian, Didi (TESLA Jurnal Teknik Elektro UNTAR, 2006)
This paper discusses about AES Rijndael, the cryptography algorithm. The security factor in delivering important information has became awareness for some people. Many ways have been issued to secure the information. One of those ways is by applying encryption using some cryptography algorithms. The algorithm itself has been improved year by year to overcome irresponsible people to get the information easily. The algorithm Rijndael were born in 1997 and chosen as new standard in cryptography world in 2000. This algorithm has been chosen not just for its security, but also because the flexibility and efficiency implementation in many platform.